Climate resilience differs across dairy sheep populations in Europe - M.J. Carabaño; V. Tsartsianidou; D. Hazard; H. Larroque; D. Buisson; C. Pineda-Quiroga; E. Ugarte; M. Serrano; M.A. Jiménez; A. Triantafyllidis; G. Arsenos; C. Díaz; et al. (Animal)
The dairy sheep sector in Europe is characterised by the wide range of breeds involved, the variety of environments and the existence of well-established selection schemes. The goal of this study was to characterise the productive response to changes in thermal load (TL) across dairy sheep breeds in Europe, both at the population and the individual levels. Milk, fat and protein test day yields data from five dairy breeds, Assaf (As), Chios (Ch), Lacaune (Lc), Latxa (Lt) and Manchega (Mn) were used. Overall, 682 972 ewes from 827 flocks participated in the study. The breeds differed in the climatic region of origin and breeding area, varying from temperate (Lc and Lt) to warm (As, Ch, Mn), and, in the intensity of the selection programmes, with As and Lc more intensely selected. Historical production data were combined with meteorological information at the date of recording. Reaction norm models with polynomial functions in mixed model settings were fitted. Substantial variability in the population response to changes in TL was observed across breeds. Mn and Ch, with similar levels of production and climatic conditions, displayed greater sensitivity to cold than to hot conditions. On the other hand, the Lt breed showed the highest tolerance to cold stress and was moderately sensitive to heat. The most productive breeds, As and Lc, showed the largest sensitivity to cold (CS) or heat (HS) stress, with As/Lc showing the greatest production loss associated with cold/heat stress. Individual variability in response to thermal stress was observed in all breeds for the two extremes. However, variability in slopes of response was substantially lower than the overall variability of the trait, ranging from 4%/°C for all traits under CS to 17%/°C for fat yield under HS, in the Lc breed. For all breeds, a negative correlation was estimated between the individual level of the traits and heat tolerance, indicating antagonism between high production and heat tolerance. However, this antagonism was mild in Mn (−0.19 or milk yield and −0.28 for fat and protein yield) and largest for Lc (−0.77, −0.96 and −0.70 for milk, fat and protein yields, respectively). Given the expected increase in temperatures associated with climate change, dairy sheep farming based on the breeds less adapted with warm conditions and also for the more intensive systems based on highly producing animals will need to implement heat abatement strategies or incorporate heat tolerance in the selection programmes to improve future adaptation.